Integration of heterologous bone matrix associated with polymethylmethacrylate in induced tibial bone defects. An experimental study in rabbits - De Freitas,Silvio Henrique (2021)
ABSTRACT Purpose To analyze and compare the reactions at the interface between the composite, composed of fragmented heterologous mineralized bone matrix (MOMHF) and polymethylmethacrylate (PMMA), and the rabbit’s tibias, through macroscopic evaluation and scanning electron microscopy (SEM) in different periods. Methods In this study, 12 New Zealand adult rabbits were used (E1: n = 3, E2: n = 3, E3: n = 3 and E4: n = 3). They had the right tibial defects filled with composite and were evaluated immediately after surgery and at 30, 60, 90, and 120 days. Results The composites were incorporated and integrated into the recipient beds in 100% of the cases, defined by the MOMHF osseointegration and the PMMA fibrointegration, with no sign of infection, migration, or rejection. Conclusions The behavior of the composites in the recipient beds demonstrates that these biomaterials have the potential to be used in bone defect repairs, offering, thus, better quality of life to the orthopedic patient.